An analysis of sugary endosperm in sorghum: Characterization of mutant phenotypes depending on alleles of the corresponding starch debranching enzyme - Hashimoto, Shumpei; Okada, Satoshi; Araki-Nakamura, Satoko; Ohmae-Shinohara, Kozue; Miura, Kotaro; Kawaguchi, Hideo; Ogino, Chiaki; Kasuga, Shigemitsu; Sazuka, Takashi (Frontiers in Plant Science, 2023)
Sorghum is the fifth most important cereal crop. Here we performed molecular genetic analyses of the ‘SUGARY FETERITA’ (SUF) variety, which shows typical sugary endosperm traits (e.g., wrinkled seeds, accumulation of soluble sugars, and distorted starch). Positional mapping indicated that the corresponding gene was located on the long arm of chromosome 7. Within the candidate region of 3.4 Mb, a sorghum ortholog for maize Su1 (SbSu) encoding a starch debranching enzyme ISA1 was found. Sequencing analysis of SbSu in SUF uncovered nonsynonymous single nucleotide polymorphisms (SNPs) in the coding region, containing substitutions of highly conserved amino acids. Complementation of the rice sugary-1 (osisa1) mutant line with the SbSu gene recovered the sugary endosperm phenotype. Additionally, analyzing mutants obtained from an EMS-induced mutant panel revealed novel alleles with phenotypes showing less severe wrinkles and higher Brix scores. These results suggested that SbSu was the corresponding gene for the sugary endosperm. Expression profiles of starch synthesis genes during the grain-filling stage demonstrated that a loss-of-function of SbSu affects the expression of most starch synthesis genes and revealed the fine-tuned gene regulation in the starch synthetic pathway in sorghum. Haplotype analysis using 187 diverse accessions from a sorghum panel revealed the haplotype of SUF showing severe phenotype had not been used among the landraces and modern varieties. This is because, for grain sorghum breeding, weak alleles (showing sweet and normal endosperm) of mutants are more valuable; therefore, we searched and identified such a mutant in the public EMS-induced library. Our study suggests that more moderate alleles (e.g. produced by genome editing) should be beneficial for improving eating quality of grain sorghum.